Rhetoric in popular culture - Brummett, Barry 1951- (SAGE, 2015)
This book provides readers with in-depth insight into the techniques of rhetorical criticism to analyze the full spectrum of contemporary issues in popular culture. From movies, magazines and advertisements, to social networking sites, music videos and television shows, this text presents key rhetorical concepts and applies them with critical analysis to a variety of exciting examples drawn from today's popular culture. Moving from theory to practice throughout the text, this book links concepts in an easy-to-understand way. This book covers the concept rhetoric, itself, as well as its place and dynamic change in history, and offers methods to effectively employ rhetorical criticism in daily life. The new edition includes pertinent critical essays and case studies that show readers how the critical methods discussed can be used to study the hidden rhetoric of extended texts, and more.